A genealogia da confissão em Michel Foucault - Italiano, Adam (2025)
Beginning with the constitutive relationship between truth and the subject in Michel Foucault's intellectual production, the dissertation analyzes a specific mode of articulation between the two aforementioned concepts: confession. To this end, two sets of texts by the philosopher are examined, highlighting the passages in which confession appears. First, the texts on the history of psychiatric practices, and then those on the history of legal practices. Throughout the work, the paradoxical role of confession is emphasized as both a technique of domination and a practice of the self. The central issue guiding the study is the possibility of thinking about a truth of the self, which, unlike confession, does not reinforce mechanisms of power but rather opposes them, constituting itself as a practice of resistance. Driven by this question, the dissertation concludes with an analysis of the author's practical, intellectual, and militant activity, particularly within the G.I.P. (Prison Information Group), which was characterized by the aim of listening to and disseminating the critical truth of prisoners, their families, and various professionals—in short, of all the bodies subjected to imprisonment who denounce it as intolerable.